Localization Of Psychology: Analytical Study for A Sample of Psychology Dissertation in Sudanese Universities - Omar Alkhaleefa; Muna Babakr (University of Science and Technology, Yemen, 2011)
Localization Of Psychology: Analytical Study for A Sample of Psychology Dissertation in Sudanese Universities Abstract This study aimed to investigate the degree of inidigenization of psychology with reference to doctorate theses that were obtained in higher education between the year (1990-1997) and (1998-2005).  To achieve this aim, content analysis was employed as a method and tool. Both stratified and simple random sample techniques were used in the selection of 50 theses and special scale was designed for measuring the degree of indigenization of psychology. The results of the study showed that there was a lack of cross-cultural discussion in the majority of theses (66%) the percentage of slight discussion (18%), average discussion (6%), high discussion (8%) and there was a single thesis with full cross-cultural discussion. The study showed that the vast majority of theses lack any form of psychological criticism to Western or modern constructs, theories, methods or local practices (90%), the percentage of slight criticism (6%), high (4%) and no single thesis with full criticism.  It showed that there were no differences in the employment of foreign constructs in the introduction section between the two terms. The percentage in each term was (68%), however, there was slight increase in term 2 (4%). With reference to the aims of the studies, it showed that there was a decrease in the international aims from (52%) in term 1 to (48%) in term 2 with a difference of 4%. The study showed no differences in citation of indigenous constructs or similar ones between the two terms (56%) each. It showed that there was an increase in the employment of local references in the discussion section from 8% in term 1 to 12% in term 2 with an increase of 4%. The study showed that there was a slight increase in cross-cultural discussion from term 1 (4%) to term 2 (8%) with an increase of 4%. Furthermore, it showed that there was an increase in the slight psychological criticism for constructs, theories and methods from term 1 (4%) to term 2 (8%) with an increase of 4%. Generally, there was slight increase of the degree of indigenization between the two terms estimated as 4%.  This increase is perhaps, due to the organization of the inaugural conference of the Sudanese Psychological Society that called for the indigenization of psychology to suit the local environment.